Kingship and consent in Anglo-Saxon England, 871-978 : assemblies and the state in the early Middle Ages - Roach, Levi, 1985- (Cambridge studies in medieval life and thought., 2013)
This is an engaging new study of how kingship and royal government operated in the late Anglo-Saxon period.